Household characteristics of persons with complex care needs in the community: A preliminary study. Issue 1 (23rd September 2020) - Yoshioka‐Maeda, Kyoko; Fujii, Hitoshi
Abstract: Aim: To identify the characteristics of households of persons with complex care needs and clarify the care period length required to resolve their primary health issues. Design: A descriptive cross‐sectional study design. Methods: We collected registered data and nursing records from 155 households living in City A within the Tokyo Metropolis. They were designated as complex care cases by the home care and life support centre and needed a multidisciplinary approach to care from April 2018–July 2019. Results: Most households comprised an elderly with a single adult child ( N  = 47, 30.3%). Mental illness and economic distress overlapped as the most common issues. The mean length of care period was 147.7 days ( SD  = 120.6). The log‐rank test showed that single persons took significantly less time to resolve their primary health issues than elders with single‐child households or single‐person <65‐year‐old households.